Divination and deity in African religions - Zuesse, Evan M. (History of Religions, 1975)
After characterizing the two basic types of divination found in traditional African religions (and a third sub-type), this phenomenological study analyzes the differing implications of "possession" and the more esoteric "wisdom" forms for the sense of selfhood, relationship to local spirits and demi-gods, and to the Supreme Being. Wisdom divination is shown to be often a previously unrecognized cult to the Supreme Being. Both basic types provide subtle, profound protests against immediate social identities and pressures. The conclusion extends this insight to the history of world religions, and points to social correlates of divination. Fa divination of the Fon is analyzed, and the role of tricksters as patrons of divination is discussed.
free
Keywords: Africa – Religion; Divination; Fon (African people); God (African religion); Spirit possession; Tricksters